Integrating internationally qualified nurses: a qualitative exploration of nurse managers’ influence from nurses’ experiences - Roth, Catharina; Breckner, Amanda; Krug, Katja; Mahler, Cornelia; Wensing, Michel; Berger, Sarah (BMC nursing, 2025)
Healthcare systems globally are confronted with a shortage of nurses. Various strategies to address this have been applied, including active recruitment of internationally qualified nurses. Nurse managers may have a central role in supporting workplace integration. This study aimed to explore how domestically qualified nurses and internationally qualified nurses viewed the role of nursing management and its impact on workplace integration.